Enhanced indexing and selectivity theory. (24th August 2021) - Bolshakov, Andrei; Chincarini, Ludwig B.; Lewis, Christopher
Abstract: Investment managers that believe to have skill must choose some fraction of stocks in a benchmark to hold. Recent theory predicts that the optimal percentage of holdings for a manager with skill is between 50% and 80% of the benchmark. This theory requires a number of assumptions. Using simulations, we relax some of the assumptions to examine if the theory still holds. We find that, for the most part, the theory holds when the assumptions are relaxed. We also extend the analysis from a one‐period horizon to a multiperiod horizon using the actual returns of stocks in the S&P 500.